Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Toltrazuril sulfone (Ponazuril) residue depletion in pig tissues and estimated withdrawal intervals - Laura M. Neumann; Farha Sheela; Hiroko Enomoto; Jeremy Pittman; Ronald E. Baynes (Regulatory Toxicology and Pharmacology, 2025)

Landscape structure affects temporal dynamics in the bumble bee virome: Landscape heterogeneity supports colony resilience - Laura Bosco; Orlando Yañez; Alexandria Schauer; Corina Maurer; Samuel A. Cushman; Raphaël Arlettaz; Alain Jacot; Torsten Seuberlich; Peter Neumann; Daniel Schläppi (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Clonidine stimulates force of contraction via histamine H2 receptors in the human atrium - Joachim Neumann; Steffen Pockes; Laura J. Humphrys; Denise Mönnich; Lisa Forster; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Clonidine has various clinical effects mediated by agonism of α 1 - or α 2 -adrenoceptors and the blocking of hyperpolarization-activated-nucleotide-gated pacemaker channels (HCN). It is unknown whether clonidine can also stimulate human cardiac histamine H 2 receptors (hH 2 Rs). We used isolated electrically stimulated left and spontaneously beating right atrial preparations from mice overexpressing the hH 2 R specifically in the heart (H 2 -TG), and spontaneously beating right atrial preparations of guinea pigs for comparison. Moreover, we studied isolated electrically stimulated muscle strips from the human right atrium. Clonidine (1, 3, and 10 µM) increased force of contraction in isolated left atrial preparations from H 2 -TG mice. In contrast, clonidine reduced the spontaneous beating rate in right atrial preparations from H 2 -TG. Clonidine raised the beating rate in guinea pig right atrial preparations. Clonidine failed to increase the force of contraction but reduced beating rate in wild-type litter mate mice (WT). In WT, histamine failed to increase the force of contraction in left atrial preparations and beating rate in right atrial preparations. Clonidine (10 µM) increased the force of contraction in isolated human right atrial preparations. The positive inotropic effect in the human atrium was attenuated by cimetidine (10 µM). Clonidine increased the beating rate of the isolated spontaneously beating guinea pig right atrium and acted as a H 2 R partial agonist. Furthermore, clonidine showed binding to the guinea pig H 2 R (100 µM) using HEK cells in a recombinant expression system (p K i < 4.5) but hardly to the human H 2 R. These data suggest that clonidine can functionally activate cardiac human H 2 R.

Lysergic acid diethylamide stimulates cardiac human H2 histamine and cardiac human 5-HT4-serotonin receptors - Ulrich Gergs; Hannes Jacob; Pauline Braekow; Britt Hofmann; Steffen Pockes; Laura J. Humphrys; Uwe Kirchhefer; Charlotte Fehse; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Lysergic acid diethylamide (LSD) is an artificial hallucinogenic drug. Thus, we hypothesized that LSD might act 5-HT 4 serotonin receptors and/or H 2 histamine receptors. We studied isolated electrically stimulated left atrial preparations, spontaneously beating right atrial preparations, and spontaneously beating Langendorff-perfused hearts from transgenic mice with cardiomyocyte-specific overexpression of the human 5-HT 4 receptor (5-HT 4 -TG) or of the H 2 -histamine receptor (H 2 -TG). For comparison, we used wild type littermate mice (WT). Finally, we measured isometric force of contraction in isolated electrically stimulated muscle strips from the human right atrium obtained from patients during bypass surgery. LSD (up to 10 µM) concentration dependently increased force of contraction and beating rate in left or right atrial preparations from 5-HT 4 -TG ( n = 6, p < 0.05) in 5-HT 4 -TG atrial preparations. The inotropic and chronotropic effects of LSD were antagonized by 10 µM tropisetron in 5-HT 4 -TG. In contrast, LSD (10 µM) increased force of contraction and beating rate in left or right atrial preparations, from H 2 -TG. After pre-stimulation with cilostamide (1 µM), LSD (10 µM) increased force of contraction in human atrial preparations ( n = 6, p < 0.05). The contractile effects of LSD in human atrial preparations could be antagonized by 10 µM cimetidine and 1 µM GR 125487. LSD leads to H 2 -histamine receptor and 5-HT 4 -receptor mediated cardiac effects in humans.

Ergometrine stimulates histamine H2 receptors in the isolated human atrium - Hannes Jacob; Pauline Braekow; Britt Hofmann; Uwe Kirchhefer; Lisa Forster; Denise Mönnich; Laura J. Humphrys; Steffen Pockes; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Ergometrine (6a R ,9 R )- N -(( S )-1-hydroxypropan-2-yl)-7-methyl-4,6,6a,7,8,9-hexa-hydro-indolo-[4,3- fg ]chinolin-9-carboxamide or lysergide acid β-ethanolamide or ergonovine) activates several types of serotonin and histamine receptors in the animal heart. We thus examined whether ergometrine can activate human serotonin 5-HT 4 receptors (h5-HT 4 R) and/or human histamine H 2 receptors (hH 2 R) in the heart of transgenic mice and/or in the human isolated atrium. Force of contraction or beating rates were studied in electrically stimulated left atrial or spontaneously beating right atrial preparations or spontaneously beating isolated retrogradely perfused hearts (Langendorff setup) of mice with cardiac specific overexpression of the h5-HT 4 R (5-HT 4 -TG) or of mice with cardiac specific overexpression of the hH 2 R (H 2 -TG) or in electrically stimulated human right atrial preparations obtained during cardiac surgery. Western blots to assess phospholamban (PLB) phosphorylation on serine 16 were performed. Ergometrine exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in atrial preparations starting at 0.3 µM and reaching a plateau at 10 µM in H 2 -TGs ( n = 7). This was accompanied by an increase in PLB phosphorylation at serine 16. Ergometrine up 10 µM failed to increase force of contraction in left atrial preparations from 5-HT 4 -TGs ( n = 5). Ten micrometer ergometrine increased the force of contraction in isolated retrogradely perfused spontaneously beating heart preparations (Langendorff setup) from H 2 -TG but not 5-HT 4 -TG. In the presence of the phosphodiesterase inhibitor cilostamide (1 µM), ergometrine at 10 µM exerted positive inotropic effects in isolated electrically stimulated human right atrial preparations, obtained during cardiac surgery, and these effects were eliminated by 10 µM of the H 2 R antagonist cimetidine but not by 10 µM of the 5-HT 4 R antagonist tropisetron. Furthermore, ergometrine showed binding to human histamine H 2 receptors (at 100 µM and 1 mM) using HEK cells in a recombinant expression system (p K i < 4.5, n = 3). In conclusion, we suggest that ergometrine is an agonist at cardiac human H 2 Rs.

Climate change and stock returns in the european market: An environmental intensity approach - Maria-Glòria Barberà-Mariné; Laura Fabregat-Aibar; Andreu-Michael Neumann-Calafell; Antonio Terceño (Journal of Environmental Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Der Eisenstoffwechsel und seine Bedeutung für das Höhentraining - Georg Neumann; Kuno Hottenrott; Laura Hottenrott (German Journal of Exercise and Sport Research, 2021)
Zusammenfassung Ein Eisenmangel und eine katabole Stoffwechsellage behindern die Zunahme des Gesamthämoglobins und damit einen Anstieg der Sauerstofftransportkapazität, sodass die Wirksamkeit des Höhentrainings herabgesetzt ist. Die Eisenhomöostase wird sehr fein durch das hepatische Hormon Hepcidin (HEPC) kontrolliert, welches die Eisenaufnahmefähigkeit der Darmzellen über ein spezielles Protein, dem Ferroportin, kontrolliert. Unter Hypoxie stimuliert das Protein HIF-1 α die Freisetzung des Erythropoitins (EPO). Unzureichende Eisenspeicher und/oder eine Vitamin-B12-Unterversorgung bei Athleten, besonders bei jungen Frauen, sind Wochen vor einem Höhentraining durch eine orale Eisen- und/oder Vitamin-B12-Substitution unter ärztlicher Kontrolle, aufzufüllen. Voraussetzung für eine leistungsfördernde Wirkung des Höhentrainings ist ein mehrmaliger Aufenthalt in mittleren Höhen von 1700 m bis 3000 m. Als Aufenthaltsdauer werden 350 h bis 500 h oder zwei bis drei Wochen empfohlen. Mangelnde Eisenverfügbarkeit und ein Energiedefizit können die Wirksamkeit des Höhentrainings negativ beeinflussen. Liegt aus medizinischer Sicht eine Eisenunterversorgung vor, dann wird zu einer oralen Supplementation vor und während des Höhentrainings geraten. Bei normaler Eisenverfügbarkeit führt die gesteigerte Hämatopoese durch EPO zur Zunahme des Gesamthämoglobins. Die Wirkung des hypoxieinduzierten Hämoglobinanstiegs ist nach dem Höhentraining auf drei bis vier Wochen begrenzt.

Advancing Ocean Governance in Marine Regions Through Stakeholder Dialogue Processes - Laura Weiand; Sebastian Unger; Julien Rochette; Alexander Müller; Barbara Neumann (Frontiers in Marine Science, 2021)
The poor state of the ocean and the transboundary nature of the marine environment require bold action by States coordinated across sectors and territorial boundaries in order to deal with the manifold challenges the ocean is facing—and with it humankind. Cooperation and coordination among States and stakeholders in marine regions have proven to be important levers for policy implementation and to strengthen ocean governance, yet remain challenging. Transparent and engaging stakeholder dialogue processes have the potential to provide guidance for the necessary transformation toward ocean sustainability and support the attainment of Sustainable Development Goal (SDG) for the ocean, SDG 14 and other interlinked ocean-related targets. The aim of this study is to review the challenges and opportunities of current collaborative efforts, namely multi-stakeholder dialogue and exchange processes, within and between marine regions to accelerate transformative action, contributing to these global goals. This paper builds on knowledge co-production and collaborative governance literature, and reviews experiences by stakeholders with ocean-related science-policy interfaces in an effort to strengthen regional ocean governance. As an exemplary case of such interfaces, this study assesses the Marine Regions Forum, a newly established inclusive dialogue and exchange platform for diverse actors from marine regions that aims to provide an informal space for joint learning and support regional action and international governance processes alike. Employing latent content analysis of interviews with experts, critical common barriers that hamper current collaborative efforts amongst stakeholders in marine regions are identified, such as fragmented governance frameworks, power and resource imbalances, and lack of meaningful stakeholder engagement. Pathways to address these challenges, such as through common goal orientation, contextualisation, inclusivity, trust building and meaningful continuous interactions are also identified. This paper concludes by discussing the value added of transparent and inclusive collaborative processes in the transformation of ocean governance toward achieving sustainability.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Larval development of Brycon amazonicus (Teleostei, Bryconidae) with a focus on locomotory, respiratory and feeding structures - Erika Neumann; Maria Carmo F. Paes; José Mário R. Mendes; Francisco Manoel S. Braga; Laura Satiko O. Nakaghi (Journal of Fish Biology, 2018)
In the present work we describe the larval development of Brycon amazonicus , with emphasis on structures linked to swimming, respiration and feeding. We monitored from larval hatching (13 h post‐fertilization) to juvenile stage. Formation of the oral cavity and differentiation of gill arches began within 4 h post‐hatching (hph) and within 11 hph the primordium of the pectoral fin appeared. At 25 hph, the head was in a rectilinear position with a terminal mouth, when the onset of tooth formation appeared. At 35 hph, gill arches were covered by the operculum and branchiostegal membrane and cusps of teeth pierced the epithelium of the premaxilla and anterior dentary region. Sharp teeth were observed in the maxilla at 171 hph and the pelvic fin primordium appeared at 243 hph, with taste buds on the tongue and the roof of the buccopharyngeal cavity. At 579 hph, all structures related to swimming and food capture were formed. Exogenous feeding of the larvae started at 29 hph, before the endogenous reserves were used up and the development of efficient swimming ability, reflecting the species' need to increasingly specialize on prey capture.

Protein O-glucosylation in Lactobacillus buchneri - Julia Anzengruber; Martin Pabst; Laura Neumann; Gerhard Sekot; Stefan Heinl; Reingard Grabherr; Friedrich Altmann; Paul Messner; Christina Schäffer (Glycoconjugate Journal, 2014)

Echoes from the Past: A Healthy Baltic Sea Requires More Effort - Aarno T. Kotilainen; Laura Arppe; Slawomir Dobosz; Eystein Jansen; Karoline Kabel; Juha Karhu; Mia M. Kotilainen; Antoon Kuijpers; Bryan C. Lougheed; H. E. Markus Meier; Matthias Moros; Thomas Neumann; et al. (Ambio, 2014)

Synthesis of ‘cineole cassette’ monoterpenes in Nicotiana section Alatae: gene isolation, expression, functional characterization and phylogenetic analysis - Anke Fähnrich; Anne Brosemann; Laura Teske; Madeleine Neumann; Birgit Piechulla (Plant Molecular Biology, 2012)